Double Trouble: A Case of Valvular Disease in Pregnancy. Issue 22 (31st May 2016) - Gandhi, Sumeet; Ganame, Javier; Whitlock, Richard; Chu, Victor; Natarajan, Madhu K.; Velianou, James L.
Abstract : Supplemental Digital Content is available in the text.